EFECTOS QUE PRODUCE LA NO REVICTIMIZACIÓN EN DELITOS SEXUALES POR SU LIMITACIÓN EN PRUEBAS - Sotomayor Pérez, Yuleydi Cecibel (2019)
The present research work is titled "Effects produced by the non-revictimization of sexual crimes due to its limitation in evidence", emerged from the analysis made to the Ecuadorian criminal legislation, regarding Article 11, number 5 of the Organic Comprehensive Criminal Code which establishes that : "The victim has the right not to be revictimized, particularly in obtaining and evaluating the evidence, including its version", thus demonstrating the violation of procedural principles of Duda in favor of the inmate and Objectivity and the right to defense, as a guarantee Fundamental of Due Process in the absence of evidence that demonstrates the commission or none of the crime. In the course of the investigation we will address that the Non-Revictimization violates the rights of the accused to be accused without sufficient evidence to reach the truth of the fact, due to the fact that sufficient and necessary skills are not carried out to demonstrate participation in the crime of which he is accused. First of all, it is necessary to determine which victim is against whom any criminal offense has been perpetrated, a definition that falls within the provisions of the constitutional and criminal regulations; but this same scope, is deeper than described, because to determine that this person was the victim of a criminal offense, it should be understood that there was a previous constitutional-legal criminal procedure, which has allowed establishing the 6 existence of the infraction and the facts raised and that person is a victim; However, even without that, with the complaint or knowledge by the Office of the Prosecutor about situations that lead to penalties of a criminal nature, the State already adopts said persons as victims of an infraction, thus leading the accused to be defined indirectly already as the author of the crime. For the fulfillment of the proposed objectives, I proceeded to carry out the theoretical, legal and doctrinal compilation, while continuing to apply comparative legislation and field research in relation to the effects of non-revictimization on sexual crimes due to lack of evidence. Likewise, the application of methods and techniques such as surveys that were aimed at legal professionals allowed me to obtain concrete criteria, with clear and precise foundations to propose reforms necessary to solve this problem. The aspects described above are studied in this paper, which concludes with the proposal of a legal proposal according to the current legal reality, aimed at the respect of constitutional mandates, with the right to defense being one of the fundamental pillars of Due Process for the protection of persons in relation to criminal proceedings, guaranteeing the effective protection of their rights and reaching a just resolution where the punitive or sanctioning power of the State observes the respect of constitutional principles, rights and guarantees.